PENGARUH KOMPETENSI, KOMITMEN ORGANISASI, DAN LOCUS OF CONTROL TERHADAP PRESTASI KERJA PEGAWAI PADA BADAN KEPEGAWAIAN DAN PENGEMBAGAN SUMBER DAYA MANUSIA KOTA SUNGAI PENUH: ADE YUSANTO, S.AP - ADE YUSANTO (LPPM STIA Nusantara Sakti, 2021)
This study aims to determine the effect of independent variables on the dependent variable. The object of this study is the employee of the Human Development Agency (BKPSDM) Sungai Sungai City. The number of samples in this study were 98 respondents. The analysis technique used is multiple linear regression. The research results obtained based on the partial test (t test) obtained: (a) There is a positive and significant effect of competence on work performance. (b) There is a positive and significant effect on commitment to work performance. c) There is a positive and significant influence of locus of control on work performance. The results of the study simultaneously showed that competence, commitment, locus of control had a positive and significant effect on work performance. And based on the coefficient of determination test (R2) the value is 0.541 or 54.1% this shows that the percentage of contribution of the independent variable competence, commitment, locus of control to the dependent variable work performance is 0.541 or 54.1%. While the remaining 45.9% is influenced by other variables outside this study.